(untitled) (Herald of the National Children’s Medical Center, 2025)
Effective pain management remains one of the key tasks in pediatric abdominal surgery. The use of opioid analgesics is associated with the risk of side effects. Multimodal analgesia using NSAIDs allows achieving adequate pain relief, reducing the level of inflammatory reactions and improving recovery.